Memory-like responses of brain microglia are controlled by developmental state and pathogen dose - Lajqi, Trim; Stojiljkovic, Milan; Williams, David L.; Hudalla, Hannes; Bauer, Michael; Witte, Otto W.; Wetzker, Reinhard; Bauer, Reinhard; Schmeer, Christian (Frontiers in immunology, 2020)
Microglia, the innate immune cells of the central nervous system, feature adaptive immune memory with implications for brain homeostasis and pathologies. However, factors involved in the emergence and regulation of these opposing responses in microglia have not been fully addressed. Recently, we showed that microglia from the newborn brain display features of trained immunity and immune tolerance after repeated contact with pathogens in a dose-dependent manner. Here, we evaluate the impact of developmental stage on adaptive immune responses of brain microglia after repeated challenge with ultra-low (1 fg/ml) and high (100 ng/ml) doses of the endotoxin LPS in vitro. We find that priming of naïve microglia derived from newborn but not mature and aged murine brain with ultra-low LPS significantly increased levels of pro-inflammatory mediators TNF-α, IL-6, IL-1β, MMP-9, and iNOS as well as neurotrophic factors indicating induction of trained immunity (p < 0.05). In contrast, stimulation with high doses of LPS led to a robust downregulation of pro-inflammatory cytokines and iNOS independent of the developmental state, indicating induced immune tolerance. Furthermore, high-dose priming with LPS upregulated anti-inflammatory mediators IL-10, Arg-1, TGF- β, MSR1, and IL-4 in newborn microglia (p < 0.05). Our data indicate pronounced plasticity of the immune response of neonate microglia compared with microglia derived from mature and aged mouse brain. Induced trained immunity after priming with ultra-low LPS doses may be responsible for enhanced neuro-inflammatory susceptibility of immature brain. In contrast, the immunosuppressed phenotype following high-dose LPS priming might be prone to attenuate excessive damage after recurrent systemic inflammation.